Settlement response of a multilayer geosynthetic-reinforced granular fill–soft soil system. Issue 6 (November 2005) - Deb, K.; Chandra, S.; Basudhar, P. K.
Abstract : The paper pertains to the development of a mechanical model to predict the behaviour of a multilayer geosynthetic-reinforced granular fill soft soil system. The granular fill and the soft soil have been idealised as a Pasternak shear layer and a layer of non-linear springs, respectively. Stretched rough elastic membranes represent the geosynthetic reinforcement layers. The non-linear behaviour of the granular fill and the soft soil is considered. Plane strain conditions are considered for the loading and reinforced foundation soil system. An iterative finite difference scheme is applied for obtaining the solution, and the results are presented in non-dimensional form. The results of the present model are compared with the results of a finite element model. Parametric studies for a uniformly loaded strip footing show the effects of various parameters on the settlement response. Significant reduction of the settlement has been observed as a result of the use of the multilayer geosynthetic reinforcement system. The non-linear model gives more accurate results than the linear model in the case of very soft soil. The top reinforcement layer is subjected to maximum mobilised tension at the centre of the loaded area. The settlement value is decreased by an amount nearly the same as the increase of modular ratio and is independent of the number of geosynthetic layers.